The seed nuclear proteome - Repetto, Ombretta; Rogniaux, Hélène; Larré, Colette; Thompson, Richard; Gallardo, Karine (Frontiers in Plant Science, 2012)
Understanding the regulatory networks coordinating seed development will help to manipulate seed traits, such as protein content and seed weight, in order to increase yield and seed nutritional value of important food crops, such as legumes. Because of the cardinal role of the nucleus in gene expression, sub-proteome analyses of nuclei from developing seeds were conducted, taking advantage of the sequences available for model species. In this review, we discuss the strategies used to separate and identify the nuclear proteins at a stage when the seed is preparing for reserve accumulation. We present how these data provide an insight into the complexity and distinctive features of the seed nuclear proteome. We discuss the presence of chromatin-modifying enzymes and proteins that have roles in RNA-directed DNA methylation and which may be involved in modifying genome architecture in preparation for seed filling. Specific features of the seed nuclei at the transition between the stage of cell divisions and that of cell expansion and reserve deposition are described here which may help to manipulate seed quality traits, such as seed weight.